THE ROLE OF SOCIAL INSTITUTIONS ON ONLINE BUSINESS DEVELOPMENT IN CIMAHI, WEST JAVA, INDONESIA - Machroni Kusuma; Mohammad Taufiq Rahman (FISIP UIN SGD Bandung, 2018)
This study traces the role of social institutions in inviting and providing models of economic growth, including in the field of micro, small and medium enterprises in the community, especially in terms of online business. This can be a potential that can provide prosperity for the community. The question arises as to how the community-based business development model in Cimahi, West Java, whether social institutions can bring the community to online business so as to grow the creative community, how the development of society in appreciating and becoming part of online business, and questions the like can be found the answer in this paper. With descriptive and qualitative methods, this study finds that social institutions play an active role in the development of online business, as well as some people are already open in pursuing social institution programs as well as the latest technological developments in the field of sales of goods and services, but there are still obstacles that should continue to be refined for the success of online business to the advanced society.